UNESCO World Heritage as an opportunity for mountain landscapes – a trigger for development not only in the Alps - Kruse, Alexandra; Paulowitz, Bernd (JOURNAL OF LANDSCAPE ECOLOGY, 2018)
Transhumance creates unique landscapes, especially in mountain regions. These landscape types, but also the herewith connected economy, are often threatened by abandonment. On the other hand, the so created landscapes and products are highly appreciated by the people – not only the tourists. Being listed as UNESCO World Heritage might be a trigger to raise awareness (also among politicians and deciders) and, more important, to motivate farmers to go ahead with their very special living conditions and to foster sense of place/proudness of the place. The process, which leads to the nomination itself, is demanding on one side, but also often a starting point to consider the region, the site differently and to develop new processes, initiate structural changes and is in the end often highly appreciated by the population.
Keywords: UNESCO World Heritage; transhumance; past for future; valorisation of natural and cultural heritage; benefit for local communities; European agricultural mountain landscapes